A Gendered Faust : the portrayal of gender in the opera Faust (1859) by Gounod (1818-1893) - Van der Mescht, Heinrich Hermann (University of Pretoria, 2014)
Dissertation (MMus)--University of Pretoria, Pretoria, 2013.